2015
DOI: 10.1183/13993003.00577-2015
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of treatment of latent tuberculosis infection in individual patients

Abstract: We aimed to develop a decision aid that estimates whether treatment of latent tuberculosis infection (LTBI) is likely to have a net gain in quality-adjusted life-years for an individual.A Markov model was developed which incorporated personalised estimates for risk of tuberculosis (TB) reactivation, TB death, quality-of-life impairments and treatment side-effects. The net effect of LTBI treatment was quantified in terms of quality-adjusted life-years gained or lost. Analyses were conducted for a representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 26 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…Decision analysis modelling has shown that the vast majority of immunocompromised patients with LTBI will benefit from LTBI treatment. 21,97 However, the decision to screen those with immunosuppressive conditions must consider a range of additional factors. The true incidence of LTBI in the specific population, and the accuracy of LTBI tests (especially the proportion of false-negative results of TSTs and IGRAs) will have a major impact on the costs and benefits of a screening programme.…”
Section: Recommendations For Immunocompromised Patientsmentioning
confidence: 99%
“…Decision analysis modelling has shown that the vast majority of immunocompromised patients with LTBI will benefit from LTBI treatment. 21,97 However, the decision to screen those with immunosuppressive conditions must consider a range of additional factors. The true incidence of LTBI in the specific population, and the accuracy of LTBI tests (especially the proportion of false-negative results of TSTs and IGRAs) will have a major impact on the costs and benefits of a screening programme.…”
Section: Recommendations For Immunocompromised Patientsmentioning
confidence: 99%
“…Individuals at risk for new infection include recent immigrants from high incidence countries and close contacts of patients with active tuberculosis disease (particularly young children or the elderly) whereas individuals at increased risk of reactivation include those with HIV, other immunosuppressing conditions (including tumor necrosis factor-a inhibitors, hematologic or solid organ malignancies, organ transplant, chemotherapy), and those with evidence of fibronodular imaging changes suggestive of healed tuberculosis [5]. Various studies suggest that a targeted testing and treatment plan is cost effective and provides both population and individual benefit for at least several of these high-risk groups [32][33][34]. Prior to treatment for LTBI, it is imperative to exclude active disease.…”
Section: Managementmentioning
confidence: 99%
“…In their recent article, D obler et al [1] described a decision aid that estimates a net benefit of treatment for latent tuberculosis infection (LTBI) in a low tuberculosis incidence environment. While the aid probably confers some clinical utility as described, its dynamic robustness could be strengthened in some important respects.…”
Section: To the Editormentioning
confidence: 99%